Online Gambling and the Violation of Maqashid Shariah: Implications for Family Communication and Economic Stability in Indonesia - Nur Saniah; Marlina; Ade Khadijatul Z. Hrp; Rahmat (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This paper examines online gambling in Indonesia from the perspective of Maqashid Shariah. Previous studies have primarily focused on its legal status, psychological effects, economic consequences, and family-related problems, while limited attention has been given to how online gambling simultaneously undermines the fundamental objectives of Islamic law. Addressing this gap, the study analyzes online gambling as a form of systemic mafsadah that threatens multiple dimensions of human welfare (maslahah). Employing a qualitative library research approach, the study analyzes scholarly publications, official reports, and relevant academic literature using qualitative content analysis. The findings demonstrate that online gambling generates interconnected harms extending beyond financial loss, eroding the protection of religion (hifz al-din), intellect (hifz al-'aql), wealth (hifz al-mal), family and future generations (hifz al-nasl), and ultimately social stability. Rather than constituting merely a prohibited form of maisir, online gambling represents a multidimensional threat that weakens the ethical, economic, and social foundations of Muslim society. This study contributes to contemporary Maqashid Shariah scholarship by proposing a systemic framework for understanding digital gambling and offers a normative basis for developing preventive policies and strengthening family resilience in the digital era.